Intensi Whistleblowing dalam Organizational Commitment dan Obedience Pressure Auditor - Gerallda, Naomi; Noviyanti, Suzy (E-Jurnal Akuntansi; Vol 30 No 6 (2020)DO - 10.24843/EJA.2020.v30.i06.p10, 2020)
Organizational commitment encourages individuals to act positively, such as by complying with applicable rules, having responsibilities, and maintaining good relations with their professional colleagues. However, auditors often get pressure from their superiors to take actions that violate the code of ethics. This study aims to determine whether the auditors' whistleblowing intention is influenced by organizational commitment and obedience pressure. This study used an 2x2 experimental design of 2x2 between subjects using the data obtained from a total of 66 auditors. The results show that the auditors had a whistleblowing intention if organizational commitment is high and obedience pressure low.  Keywords: Obendience Pressure; Organizational Commitment; Whistleblowing.